PERENCANAAN GEOMETRIK JALUR GANDA KERETA API LINTAS STASIUN ARJASA HINGGA STASIUN KALISAT (KM. 203 + 170 -KM. 214 + 200) - Syafira Salsabilla; Nugroho Utomo; Aulia Dewi Fatikasari (Racic : Rab Construction Research, 2026)
Indonesia, as a country with vast territory and a continuously growing population, faces significant challenges in providing adequate transportation infrastructure. Railways have become one of the most preferred modes of transportation among the public, making the improvement of railway line capacity an urgent necessity particularly along the southern Surabaya–Banyuwangi corridor, which has not yet been fully developed into a double track. One such segment is the line from Arjasa Station to Kalisat Station. On this segment, train frequency remains limited due to the single-track configuration, which impacts various sectors. This study focuses on the Arjasa–Kalisat segment, which includes three stations: Arjasa, Kotok, and Kalisat. The objective of this research is to evaluate the line’s transport capacity and geometric track design as part of the efforts to develop a double-track railway. The analysis shows that the transport capacity of the segment reaches 3,983,126 tons per year and is classified as a Class IV railway. This segment uses R.54 type rails with a gauge of 1,067 mm, comprising 13 horizontal curves with radii ranging from 270 to 850 meters, and 23 vertical curves with a radius of 6,000 meters. These findings provide a crucial foundation for planning future railway infrastructure improvements to support smooth mobility and regional economic growth.